What do Alevi Rituals Tell us about the Economic Mentality? - Boz, Çiğdem (Journal of Alevism-Bektashism Studies, 2022)
In Turkey’s economic history studies, the relationship between religion and economic structure is generally analyzed from the Weberian point of view. From this point of view, the incarnation of capitalism as a system; It became possible with the emergence of the profit-oriented, rational human type (homo economicus) on the stage of history. It is the Protestant ethic that shapes the human type in question and its economic mentality. According to the Weberian view, which approaches capitalism with a system of values such as self-control, honest hard work, and continuous investment of the earned income, the absence of this type of person in Eastern societies is explained by the economic mentality of these societies that emphasizes frugality. The missing aspect of the Turkish economic history studies that deal with this Sufi-based mentality is that they put the understanding of “orthodox Sufism” in the center and exclude heterodox Sufi teachings such as Alevism, Bektashism and Melâmî culture. Righteous inquiries about why the Ottomans could not pass to capitalism unfortunately overshadowed heterodox teachings that could be seen as resistance to capitalism. Modern economics has left the analysis of these societies to anthropologists, as it sees such organizations as “irrational” due to factors such as religion or belief, which have a high impact on the organizational forms of pre-capitalist societies. The most important reason for this is that while in pre-modern societies, the economy is not immune from society and is inherent in it, in the modern era, the economy is dissembedded. In this study, the institutions and rituals of traditional Alevism, which emerged as an alternative social organization in the pre-capitalist period, will be discussed in terms of economic mentality, and Alevi rituals such as cem, sacrifice, companionship, visits are not a phenomenon that can be understood only with spiritual beliefs and values, but are egalitarian. It will also be claimed that it contains the material foundations of achieving a social structure. As an objection to the economic mentality analyzes that are often romanticized and pacified with the motto of “one bite, one cardigan”, it will be argued that the socio-economic basis of the heterodox Sufi schools in the Ottoman geography is the stateless, mutual gift-based kinship society structure.